(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
This paper investigates the thematic, structural, and ethical transformations in Karakalpak narrative poetry following national independence, focusing on Abilqasim Otepbergenov’s landmark dastan titled Allan’di Umitpa! (Do Not Forget Your Allah!). Emerging after decades of Soviet-era atheistic constraints, the work represents a pioneering effort to integrate Islamic theology, moral philosophy, and Eastern masnavi poetic forms into written Karakalpak literature. Through a systematic analysis of its 608 ten-line stanzas, this study demonstrates how Otepbergenov synthesized personal autobiographical trauma, folkloric motifs of divine intervention (ayan), historical accounts of Sufi saints like Najmetdin Qubra, and modern social critiques regarding environmental degradation and moral decay. The findings establish that Otepbergenov elevated Islamic ethics to a primary structural principle, establishing a new conceptual trajectory for contemporary Karakalpak lyro-epic poetry.